Directivity Enhancement of a Circular Microstrip Antenna with Shorting Post. Issue 1 (2nd January 2022) - Rathod, S. M.; Awale, R. N.; Ray, K. P.; Kakatkar, S. S.
Abstract : A technique of loading shorting posts on the patch has been used to enhance the directivity of a circular microstrip antenna (CMSA) in this paper. The shorting posts connected between the patch and the ground plane, force the electric field to become zero at that point, thereby modifying various modes of the circular patch. The shorting posts, also perturb the surface current distribution on the patch that help to increase its electrical size, which – in turn – enhances directivity at fixed resonance frequency. Investigations on various radii and positions of the shorting posts – to enhance the directivity of a CMSA, have been carried out. A systematic analysis on the performance of the CMSA at a lower order mode, fundamental mode and higher order mode frequencies with the loading of shorting posts has also been presented. The simulated and measured results show that the directivity of CMSA can be enhanced by up to 2 dB using the proposed technique without changing the patch geometry. In addition, the proposed antenna configuration yields, a bandwidth enhancement of almost three times as compared to that of a conventional CMSA. The simulated results of the conventional and shorted CMSA are experimentally validated with good agreement.